Striking differences in the biological and molecular properties of onion and garlic isolates of onion yellow dwarf virus - Celli, Marcos Giovani; Torrico Ramallo, Ada Karina; Kiehr, Mirta; Conci, Vilma Cecilia (Springer, 2018)
Complete nucleotide (nt) and deduced amino acid sequences of two onion yellow dwarf virus (OYDV) isolates showing mild and severe symptoms in onion but being unable to infect garlic were determined. The genomes consisted of 10,459 and 10,461 nt (without the 3’ poly(A) tail) and were 92.2 % identical. Comparison of their whole genomes, polyproteins and P1, HC-Pro, P3, CI, VPg and NIa-Pro regions with those of garlic isolates previously identified as OYDV gave percentage values below that proposed as the molecular threshold for potyvirus species demarcation. This and the striking differences in host range between onion and garlic isolates suggest that they represent different virus species.